Wilson : the struggle for neutrality, 1914-1915 - Link, Arthur S. (Arthur Stanley), 1920-1998 (Princeton legacy library., 1960)
Critics have called the two prior volumes in this life of Woodrow Wilson "a model of political biography" (Arthur M. Schlesinger, Jr.), and "a capital piece of work, critical and judicious" (Henry Steele Commager). In this third volume Arthur Link covers the period between the immediate background of World War I and the not, to Great Britain of October 21, 1915, marking the end of Wilson's fight to lay solid foundations for American neutrality. Volume 3 also adds new material on American involvement in Mexico, the Caribbean and the Far East. A less stern picture of Wilson emerges-the picture of man struggling patiently and cautiously to avoid entanglement in the European war, work out a reasonable adjustment to British sea power, and meet the German challenge of submarine warfare in a mod rate restrained manner.Originally published in 1960.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.